2015
DOI: 10.1017/s1751731114002833
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and its heritability in Corriedale and Merino lambs

Abstract: Temperament can be defined as the fearfulness and reactivity of an animal in response to humans and strange, novel or threatening environments. The productive performance of an animal is affected by its temperament, and selection of calm animals might improve their adaptation to the farming environment and handling, as well as improve productivity. The temperament was measured in lambs of two breeds of sheep in Uruguay. The effects of dam's age, type of birth, age of the lamb and contemporary group (CG; lambs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…The ock is kept at the UWA Farm Ridge eld, Pingelly, Western Australia. The temperament of the sheep in the ock was assessed within two weeks after weaning at around 16 weeks of age using two behavioural tests that are described in detail below under phenotyping of sheep temperament [6]. An overall selection score was calculated for each animal by combining the results of two tests [9].…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ock is kept at the UWA Farm Ridge eld, Pingelly, Western Australia. The temperament of the sheep in the ock was assessed within two weeks after weaning at around 16 weeks of age using two behavioural tests that are described in detail below under phenotyping of sheep temperament [6]. An overall selection score was calculated for each animal by combining the results of two tests [9].…”
Section: Animalsmentioning
confidence: 99%
“…Isolation box test: Within two minutes after the completion of the arena test, each sheep was introduced into, and locked in, an enclosed wooden box (H: 1.5 m × L: 1.5 m × W: 0.75 m) and left for one min while deprived of visual contact with conspeci cs [6]. The level of vibration of the box that was produced by the movement of sheep and the high pitch bleats were recorded by an apparatus (agitation meter) that was xed to the outside of the box [8].…”
Section: Genotyping Of Snpsmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported moderate level of heritability for the temperamental trait [ 6 ]. In sheep, Zambra et al [ 7 ] demonstrated that the temperament of Uruguayan Merino and Corriedale sheep is moderately heritable. In cases of horses, there is a study estimated genetic parameters for the behavioral response of Thoroughbred horses at medical checkups for horseracing [ 8 ].…”
Section: Introductionmentioning
confidence: 99%